Reduction of Opioid Prescriptions in Maxillofacial Trauma Following North Carolina STOP Act. Issue 3 (September 2021) - Curtis, Caitrin; Scarcella, Joshua; Viscardi, Chelsea; Samia, Arthur; Zeri, Richard; Guo, Yifan
Study Design: Retrospective cohort study Objective: On January 1, 2018, the Strengthen Opioid Misuse Prevention (STOP) Act was implemented to increase oversight over opioid prescriptions in North Carolina. The aim of this study is to evaluate the legislation's efficacy in reducing opioid prescriptions following facial fracture repair. Methods: A retrospective chart review of patients who sustained maxillofacial fractures and underwent repair from January 1, 2015 through December 31, 2019 at a level 1 trauma center was performed. The North Carolina Controlled Substance Database was used to quantify perioperative opioid prescriptions in morphine milligram equivalents (MME). Average MME per patient was compared between 2 groups, patients who underwent surgery before the NC STOP Act came into effect and patients who underwent treatment after. This comparison was also performed on case type subgroups including surgically treated fractures of the orbit, mandible, midface, and multiple regions. A student's t-test was used to compare before and after groups in all analyses. Results: Of the 253 patients who met inclusion criteria, 146 were in the before group, and 107 were in the after group. There was a statistically significant, 30.9% decrease in overall average MME prescribed after the NC STOP Act was enacted. A statistically significant decrease was noted in patients who had facial fractures of multiple regions. Conclusion: Since the implementation of the NC STOP Act in 2018, there have been statistically and clinically significant decreases in the amount of opioids prescribed following surgical management of facial fractures.